The Role of National Defense Education in Fostering Love for the Homeland Among Generation Z - Angelia, Inge; Anggreni, Silvia; Indrawadi, Junaidi; Fatimah, Fatia (Journal of Moral and Civic Education, 2024)
The phenomenon of citizenship transfer that occurs at this time is evidence of a lack of love for the country, this is one of the impacts of technological development and globalisation. The generation born in the digital era is known as generation Z, which is a generation that is very vulnerable to influences from other countries. This article aims to describe the role of State Defense Education on the Attitude of Love for the Homeland in generation Z. The research method used is Mix Method, Data collection using quantitative methods is to see the relationship between state defense education on the attitude of love for the homeland in generation Z which is analysed using univariate and bivariate analysis with the Chi Square test with 266 respondents. While qualitative data collection is to see the description of how the role of state defence education on the attitude of patriotism in generation Z through observation and in-depth interviews with 10 research informants. The results showed that more than half (59%) of the respondents had a negative attitude towards the homeland, less than half (46.6%) of the respondents had never received state defence education. Based on the results of the Chi Squere test, it is found that there is a relationship between state defence education and the attitude of loving the country of generation Z with a P-Value of 0.0001. And based on the findings of the researchers, it is found that many generation Z at this time have a negative attitude of love for the country because of the many spectacles from abroad caused by the easy access that generation Z has due to technological developments. Therefore, in order to increase the sense of love for the country owned by generation Z, it is necessary for the government to make policies to be able to provide systematic state defence education to the younger generation.